The Distribution and Origins of Pyrus hopeiensis-“Wild Plant With Tiny Population” Using Whole Genome Resequencing - Li, Yongtan; Zhang, Jun; Wang, Shijie; Zhang, Yiwen; Yang, Minsheng (Frontiers in Plant Science, 2021)
Pyrus hopeiensis is a valuable but endangered wild resource in the genus Pyrus. It has been listed as one of the 120 wild species with tiny population in China. The specie has been little studied. A preliminary study of propagation modes in P. hopeiensis was performed through seed propagation, hybridization, self-crossing trials, bud grafting, branch grafting and investigations of natural growth. The results showed that the population size of P. hopeiensis was very small, the distribution range was limited, and the habitat was extremely degraded. In the wild population, natural hybridization and root tiller production were the major modes of propagation. Whole genome re-sequencing of the 23 wild and cultivated accessions from Pyrus species collected was performed using an Illumina HiSeq sequencing platform. The sequencing depth range was 26.56x–44.85x and the average sequencing depth was 32x. Phylogenetic tree and principal component analyses (PCA) based on SNPs showed that the wild Pyrus species, such as PWH06, PWH07, PWH09, PWH10, PWH13 and PWH17, were closely related to both P. hopeiensis HB-1 and P. hopeiensis HB-2. Using these results in combination with morphological characteristics, it speculated that P. hopeiensis populations may form a natural hybrid group with frequent gene exchanges between and within groups. A selective elimination analysis on the P. hopeiensis population were performed using Fst and π radio and a total of 381 overlapping genes including SAUR72, IAA20, HSFA2 and RKP genes were obtained. These genes were analyzed by gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) function enrichment. And four KEGG pathways, including lysine degradation, sphingolipid metabolism, other glycan degradation and betaine biosynthesis were significantly enriched in the P. hopeiensis population. Our study provided information on genetic variation, evolutionary relationships and gene enrichment in P. hopeiensis population. These data will help reveal the evolutionary history and origin of P. hopeiensis and provide guidelines for subsequent research on the locations of functional genes.